Pelatihan Fotografi dan Videografi melalui Handphone untuk UMKM - Yuliawan, Rahmat; Shakila, Aurora; Syah, Aurora (Universitas Serang Raya, 2025)
This digital world has created a new economic situation. Entrepreneurs and traders do not only sell and promote their products and services through offline. However, now everything is implemented in a hybrid form (online and offline). Starting from promoting the product or service on social media, websites, to e-commerce. Digital commerce has unlimited time and space. It is inversely different from offline trade which has space and time limitations. So that in digital marketing, the presentation of products or services must be packaged properly and can convey the message and value of the product or service. Therefore, a workshop activity with the theme